2022
DOI: 10.3389/fmicb.2022.907631
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of Ulcerative Cutaneous Leishmaniasis by Leishmania (Viannia) panamensis to Investigate Infection, Pathogenesis, Immunity, and Therapeutics

Abstract: A mouse model of cutaneous leishmaniasis (CL) by Leishmania (Viannia) panamensis (L(V)p) that reproduces the characteristics of the human disease remains elusive. Here we report the development of a CL model that uses a mouse-adapted L(V)p isolate to reproducibly induce a dermal disease with a remarkable similarity to human CL. BALB/c mice infected intradermally in the ear with 105 stationary UA-946 L(V)p promastigotes develop a progressive cutaneous disease that exhibits the typical ulcerated lesions with ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
0
3
0
2
Order By: Relevance
“…To verify whether parasite antimony resistance might influence myeloid recruitment at the site of L. (V.) panamensis infection, we used a BALB/c mouse model that reproduces the immune response in human CL infection caused by this Leishmania species. 31 Neutrophils are among the first cells recruited to the site of infection, and their rapid cytokine release modulates the recruitment of other cells 32 , 33 , 34 , 35 , 36 ; we thus first assessed whether murine bone marrow neutrophils (BMNs) isolated from BALB/c mice respond to clinical Leishmania strains having distinct antimony susceptibility in a similar way as human neutrophils. We observed an increased ROS production in murine BMNs exposed to MA S parasites compared with those infected with MA R strains ( Figure 5 A), concurring with previous findings reported in human neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…To verify whether parasite antimony resistance might influence myeloid recruitment at the site of L. (V.) panamensis infection, we used a BALB/c mouse model that reproduces the immune response in human CL infection caused by this Leishmania species. 31 Neutrophils are among the first cells recruited to the site of infection, and their rapid cytokine release modulates the recruitment of other cells 32 , 33 , 34 , 35 , 36 ; we thus first assessed whether murine bone marrow neutrophils (BMNs) isolated from BALB/c mice respond to clinical Leishmania strains having distinct antimony susceptibility in a similar way as human neutrophils. We observed an increased ROS production in murine BMNs exposed to MA S parasites compared with those infected with MA R strains ( Figure 5 A), concurring with previous findings reported in human neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is important to highlight the divergent results in the scientific literature regarding important issues, such as dosage, quantity of inoculated Leishmania (10 5 –10 7 ), and the model of cutaneous leishmaniasis employed (ear pinna, hind footpad or tail base), all of which may influence disease severity and outcome, as well as pharmacologic response ( Loeuillet et al, 2016 ; Paladi et al, 2017 ; Coelho et al, 2016 ; Kauffmann et al, 2018 ). Most studies that have observed reduced parasite burden employed daily doses between 16.8 mg/Sb 5+ /kg/day and 200 mg/Sb 5 +/kg/day, or once a week at 500 mg/Sb 5+ /kg/week ( Paladi et al, 2017 ; Brustolin et al, 2022 ; Muñoz-Durango et al, 2022 ). Herein, Glucantime ® was administered at a dose of 50 mg/Sb 5+ /kg/day to treat animals infected with 10 6 stationary promastigotes in the ear dermis, which was designed to ensure the development of highly parasitized, non-healing and inflamed lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Camundongos são, em geral, hospedeiros pobres ou não permissivos para espécies do subgênero Viannia, como L. braziliensis, L. panamensis e L. guyanensis, responsáveis pela maioria das doenças cutâneas e mucocutâneas nas Américas. Em contrapartida, o hamster sírio (Mesocricetus auratus) é altamente suscetível a essas espécies, com a ocorrência de lesões ulcerativas e crônicas, muito similares com as úlceras observadas em humanos, demonstrando bons resultados ao induzir lesões cutâneas causadas por L. braziliensis (GOMES-SILVA et al, 2013) e L. panamensis (MUÑOZ-DURANGO et al, 2022). Entretanto, seu uso ainda é limitado devido à baixa disponibilidade de anticorpos específicos para hamsters para estudar o papel da resposta imune na doença (GOMES-SILVA et al, 2013).…”
Section: Discussionunclassified
“…Dada a importância da LT no Brasil, o estabelecimento de modelos experimentais animais para estudo da doença faz-se necessário, de forma a permitir a elucidação de seus mecanismos subjacentes. Dentre os principais modelos utilizados encontram-se os camundongos e hamsters, que possibilitam a investigação das interações entre o parasita e o sistema imunológico do hospedeiro, bem como o aprofundamento do entendimento da patogênese da doença (SACKS; MELBY, 2015;MUÑOZ-DURANGO et al (2022). Dessa forma, o objetivo do presente trabalho foi realizar uma revisão bibliográfica acerca dos modelos experimentais disponíveis para o estudo da LT, apresentando as diferenças encontradas entre espécies do parasito, espécies e linhagens dos animais, procedendo posteriormente com a discussão dos achados.…”
unclassified